Consult, Consent and Veto: International Norms and Canadian Treaties - Imai, Shin (Osgoode Digital Commons, 2016)
Large parts of Canada, from Ontario to parts of British Columbia and north to the Northwest Territories, are covered by the “numbered treaties”, signed between First Nations and the Crown between 1871 and 1929. These treaties provide for the creation of small reserves for the Indians, and the “surrender” of the remaining tracts of land to the Crown. The land that is “surrendered” continues to be available for Indigenous hunting, fishing and harvesting activities. However, once the land is “taken up” by the provincial Crown for activities such as mining, lumbering and settlement, the treaty rights to hunt, fish and harvest are suppressed. The Supreme Court of Canada has said that the “taking up” of lands cannot go so far as to leave no “meaningful right” to hunt, fish and harvest. This article argues that the Crown should enter into negotiations to determine which territories should be preserved for the harvesting activities guaranteed by the treaty. In the meantime, courts should ensure that First Nations consent to further development on their traditional territories.